Korean Sa-Ahm Acupuncture for Treating Canine Oral Fibrosarcoma - Keum Hwa Choi; Kristi Flynn (Medical Association of Pharmacopuncture Institute, 2017)
A nine-year-old male neutered Golden Retriever presented with oral fibrosarcoma. Sa-Ahm Traditional Korean acupuncture was provided along with medicinal herb treatment. Based on Sa-Ahm's theory, the constitution of this case was hypoactive Large-Intestine (LI) meridian qi. The acupuncture treatment was focused on reinforcing LI meridian qi along with reinforcing Small-Intestine and Liver meridian qi. The necrosis of the tumor started from 8 months after treatments and was completely necrotized around 1 month after initiation of tumor necrosis. Karnofsky Performance Status score was 80 to 100 % throughout the treatment except during the active stage of tumor necrosis having KPS of 50%. In this study, oral fibrosarcoma was managed well by both Sa-Ahm acupuncture and medicinal herb treatment. The result suggested that Sa-Ahm acupuncture along with herbal treatment could be a potential medical option for canine oral FSA therapy.